Accountability of Cyber Actors for Disseminating SARA-Based Information under Law Number 19 of 2016 and the Criminal Code: Study: Decision Number 73/Pid.Sus/2021/PN NGA - Rumapea, Mazmur Septian; Br.Siahaan, Nadia Octavia Putri (International Journal of Business, Law, and Education, 2025)
Cybercrime utilizes the development of information technology to commit crimes, including the dissemination of racially charged information that can lead to social conflict and disruption of community stability. This research identifies legal gaps in the criminal liability of cyber offenders as well as challenges in collecting digital evidence. The lack of clear legal boundaries and various obstacles in law enforcement in the digital realm are the main focus. Through the normative juridical method, this research examines the law as a norm that applies in society based on the hierarchy of legislation and the harmony of legislation. The case example discussed is the phishing crime by Rizki Fahmi, the defendant of spreading SARA hatred. Firm and consistent law enforcement is needed to overcome cybercrime and its significant impact on victims and the wider community.